Standardization of PCR technique for detecting Listeria monocytogenes in chicken, beef and pork - De la Rosa Zariñana, Asael Edem; Crosby-Galván, María M.; Ramírez-Guzmán, Martha E.; Hernández-Sánchez, David; Mata-Espinoza, Miguel A. (Ecosistemas y Recursos Agropecuarios, 2018)
The aim of this study was to standardize the PCR technique for detecting Listeria monocytogenes (Lm) in chicken, beef and pork. The sensitivity and specicity of PCR and the level of concordance with the microbiological method were evaluated. PCR was standardized using a total of 60 samples of chicken, beef and pork (20 samples per meat type.) Sensitivity and specicity were calculated using the 2 x 2 table and the level of accordance by the Kappa index. The minimum detectable DNA concentration was 3.0 ng L????1. The PCR showed 100% sensitivity andspecicity, and 80, 91 and 100% concordance between the methods was obtained for detecting Lm in chicken, beef and pork samples respectively, with 89.4% similarity between the methods for the three types of meat.